UJI PATOGENESITAS Ustilago scitaminea PENYEBAB PENYAKIT LUKA API TERHADAP BEBERAPA VARIETAS TANAMAN TEBU (Saccharum officinarum L.) - ASNIAH, ASNIAH; AYUNI, RANI; SYAIR, SYAIR; TAUFIK, MUHAMMAD; RAHMAN, ABDUL; SATRAH, VIT NERU; BOTEK, MUHAMMAD; PUTRI, NOVITA PRAMASARI (Jurnal Agroteknos, 2023)
Burn disease caused by the fungus Ustilago scitaminea is an airborne pathogen whose spores can be carried by the wind, agricultural tools and people who wear the clothes they wear. The use of resistant varieties is a fairly effective control in controlling smut disease in sugarcane. This study aims to determine the resistance response of sugarcane varieties to smut disease on sugarcane (Saccharum officinarum L.). This research was conducted at the Laboratory of Plant Protection, Phytopathology Unit, Faculty of Agriculture and the Green House of the Faculty of Agriculture, University of Halu Oleo, Kendari. The research design used a completely randomized design (CRD) consisting of 4 varietal treatments namely the Kidang Kencana variety (V1), the Bululawang variety (V2), the green sugarcane cultivar (V3) and the red sugarcane cultivar (V4). The results of this study indicated that disease incidence and disease severity had no significant effect at all observation times (7, 14, 21, 28, and 35 DAP). The longest incubation period with the incidence and severity of the disease was 0% in the V1 and V2 treatments.